Letter from Carl D. Duncan to Patricia Whiting, October 2, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan compliments Whiting's personality, mentions meeting with a former student and witnessing a house fire on 5th street.